Penerapan Mikroskop Digital dengan Bantuan Smartphone Android sebagai Media Pembelajaran IPA - Santy Handayani (Universitas Indraprasta PGRI Jakarta, 2019)
Microscope is the main tool to make observation and research in the field of science, because it can be used to make small objects look great observation. Faced with the limitation of learning tools, the teachers are required to have creativity assemble instructional media if not yet available. As an alternative to microscopy, performed a simple microscope manufacture with an android smartphone and used as a learning tool in the observation of onion cells. To determined the success of the manufacture and use of the simple microscope was conducted research to students of class VII as many 2 class of 50 students at Trisoko Junior School in East Jakarta. After seeing of a demonstration steps to create and used with an android smartphone, the students can immediately practice making and using it. The result showed that overall students managed to make a microscope with the help of an android smartphone with skill and neatness.